English Teachers’ Perceptions And Practices of Integrating ICT in ELT - Bhandari, Bhim Lal (Butwal Campus Journal, 2020)
This study explores the English language teachers’ perceptions and practices of information and communications technology (ICT) in ELT incorporating key skills. Furthermore, it investigates the benefits and challenges of integrating ICT. The study was carried out within the theoretical framework of constructivism theory. The study adopted the interpretive research paradigm to bring lived experiences of the participants. To achieve the purpose of the study, four teachers were purposively selected as the participants. In-depth interview was used as major technique for collecting information. The study reveals that the English language teachers have good and positive perception of integrating ICT skills as they involve students in cognitive engagement through ICT tools and devices. The study contributes to enhance students’ creativity and better language proficiency in English. Moreover, lack of sufficient ICT knowledge and skills of teachers, limited resources and infrastructure in schools, lack of ICT trainings have been realized as challenges for effective integration of ICT in English.